Effect of changes of work stress electric drive crusher - Kutsenko, Y. (Energy and Automation, 2015)
The influence of voltage fluctuation on the angular velocity of crushers. The possibility of direct start electric motor crushers and stability conditions of electric motors working in a production environment.